The predictive value of models of neuromuscular disorders to potentiate clinical translation - Maaike van Putten (The Company of Biologists, 2022)
Neuromuscular disorders (NMDs) are a heterogenous group of rare inherited diseases that compromise the function of peripheral nerves and/or muscles. With limited treatment options available, there is a growing need to design effective preclinical studies that can lead to greater success in clinical trials for novel therapeutics. Here, I discuss recent advances in modelling NMDs to improve preclinical studies as well as two articles from this issue that work in parallel to enable a deeper understanding of a particularly rare NMD, known as X-linked myotubular myopathy.